(untitled) (Journal of the College of Basic Education, 2022)
The present work involved synthesis of several new N- Trimethoprim derivatives imides on polymeric chain by two steps. The first step involved preparation of N- sub or unsub benzoyl and sub unsub acetyl amidyl sub trimethoprim (1-5) by condensation of trimethoprim drug with many substituted acid chloride. Then the second step include. Preparation new five N- (acrly–N–sub or unsub benzoyl) imidyl substituted trimethoprim (6-10) by reaction of poly acryloyl chloride with the prepared compound (1-5) in first step in a suitable solvent in the presence amount triethylamine (Et3N) with heating. The structure confirmations of all polymers were confirmed using FT-IR, 1H-NMR,13C-NMR and UV.Spectroscopy. Other physical properties including softening pointsʹ, melting point, and solubility of the polymers were also measured.